2018
DOI: 10.1021/acs.est.8b00903
|View full text |Cite
|
Sign up to set email alerts
|

Uranium Retention in a Bioreduced Region of an Alluvial Aquifer Induced by the Influx of Dissolved Oxygen

Abstract: Reduced zones in the subsurface represent biogeochemically active hotspots enriched in buried organic matter and reduced metals. Within a shallow alluvial aquifer located near Rifle, CO, reduced zones control the fate and transport of uranium (U). Though an influx of dissolved oxygen (DO) would be expected to mobilize U, we report U immobilization. Groundwater U concentrations decreased following delivery of DO (21.6 mg O/well/h). After 23 days of DO delivery, injection of oxygenated groundwater was paused and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 99 publications
0
16
0
Order By: Relevance
“…This behavior has implications for U mobility in the subsurface. Previously, oxidation of U­(IV) has been posited as a mechanism by which U is released in contaminated anoxic subsurface environments. , However, depending on the redox-buffering capacity of the sediment, U­(IV) can persist during influxes of oxidants, such as O 2 and NO 3 – . ,, An additional mechanism of U mobilization from anoxic sediments is therefore needed to explain persistent elevated groundwater concentrations. We suggest two possibilities: first, adsorbed U­(IV), whether complexed by OM or clay mineral surfaces, could be mobilized by desorption; in particular, by HCO 3 – /CO 3 2– , which solubilizes nonmineral forms of U­(IV) .…”
Section: Resultsmentioning
confidence: 99%
“…This behavior has implications for U mobility in the subsurface. Previously, oxidation of U­(IV) has been posited as a mechanism by which U is released in contaminated anoxic subsurface environments. , However, depending on the redox-buffering capacity of the sediment, U­(IV) can persist during influxes of oxidants, such as O 2 and NO 3 – . ,, An additional mechanism of U mobilization from anoxic sediments is therefore needed to explain persistent elevated groundwater concentrations. We suggest two possibilities: first, adsorbed U­(IV), whether complexed by OM or clay mineral surfaces, could be mobilized by desorption; in particular, by HCO 3 – /CO 3 2– , which solubilizes nonmineral forms of U­(IV) .…”
Section: Resultsmentioning
confidence: 99%
“…However, as noted above, the oxidation of soil layers occurred several weeks after the water table dropped below them, whereas the onset of reducing conditions was almost immediate upon water saturation during the spring flood (Figure 1). This hysteresis effect indicates that the TRZ is considerably more resilient to oxidation than to reduction, as has been noted at other similar sites (Noël et al, 2017a(Noël et al, ,b, 2019Dwivedi et al, 2018;Pan et al, 2018). The buffering capacity against re-oxidation has been explained by a combination of slow diffusivity and high oxygen consumption rates driven by microbial respiration of organic C (Pan et al, 2018) and abiotic oxidation of reduced species, such as iron monosulfides, FeS (Noël et al, 2017a(Noël et al, ,b, 2019.…”
Section: Seasonal Trendsmentioning
confidence: 67%
“…This hysteresis effect indicates that the TRZ is considerably more resilient to oxidation than to reduction, as has been noted at other similar sites (Noël et al, 2017a(Noël et al, ,b, 2019Dwivedi et al, 2018;Pan et al, 2018). The buffering capacity against re-oxidation has been explained by a combination of slow diffusivity and high oxygen consumption rates driven by microbial respiration of organic C (Pan et al, 2018) and abiotic oxidation of reduced species, such as iron monosulfides, FeS (Noël et al, 2017a(Noël et al, ,b, 2019. This is likely also the case for the Riverton TRZ where the HCl-extractable Fe(II) increased after the flood (Supplementary Figure S4), indicating an accumulation of "reactive" Fe(II) minerals, such as FeS.…”
Section: Seasonal Trendsmentioning
confidence: 67%
See 1 more Smart Citation
“…Shallow alluvial aquifers constitute important groundwater resources that are highly influenced by hydrologic changes and anthropogenic activities (e.g., irrigation, fertilizer and pesticide applications, mining-related activities). Alluvial aquifers also typically exhibit a multitude of sediment interfaces as a result of changing deposition conditions during their formation. Subsurface interfaces generate sharp gradients in physicochemical properties (e.g., redox conditions, mineralogical and organic matter composition, hydraulic conductivity) and, as a consequence, have a disproportionately large influence on biogeochemical processes. Previous studies have shown that groundwater chemistry in shallow alluvial aquifers is strongly influenced by the presence of organic-rich, fine-grained, and predominantly anoxic layers or lenses in otherwise coarse-grained and predominantly oxic aquifers. This effect has primarily been attributed to anaerobic microbial activity occurring in the fine-grained, organic-rich zones and subsequent export of reduced aqueous products to the coarse-grained aquifer. Recent field- and laboratory-based experiments suggest that reducing conditions develop in the coarse-grained zones downstream of the fine-grained lenses or layers. Sustained development of anoxic conditions in the aquifer is beyond what can be explained by the export of reduced aqueous products and their downstream abiotic reactions.…”
Section: Introductionmentioning
confidence: 87%